Identifying and prioritizing the stakeholder linkages of dairy-based farmer producer companies in India: An analytical hierarchy process - KUMAR, SUNIL; SANKHALA, GOPAL; R, SENDHIL; KAR, PRIYAJOY; SHARMA, PH. ROMEN; RAJESH (The Indian Journal of Animal Sciences, 2023)
The present study was proposed to identify stakeholders involved in the formation of FPCs, as related to the dairy-based farmer producer companies. The proposed study was conducted in Uttar Pradesh, Rajasthan, and Madhya Pradesh, as these three states are the major milk-producing states of India as well as have the highest number of dairy-based farmer producers. Four farmer producer companies from each state were selected randomly, based on three criterias. The sample size was 90 (60 officials of FPCs and 30 experts) for the study. The data were collected from primary and secondary sources. A semi-structured interview schedule based on the Satty,s nine continuum scale was developed to collect data related to stakeholder analysis. The study reported that 12 stakeholders were actively involved in the formation of FPCs. The farmers were the most important stakeholder and got the first rank in the AHP priority ranking.The linkage among the stakeholders were found medium to strong. Interest influence matrix categorized stakeholders into Key players, Context setters, Subjects and Crowd. The study suggests that there is a huge need to enhance and coordinate the backward and forward linkage among stakeholders for developing a sustainable ecosystem for the long-term viability of FPCs.